PENGARUH TERAK BAJA DAN BOKASHI SEKAM PADI TERHADAP AIR TERSEDIA, BIOMASSA TANAMAN SERTA KORELASINYA PADA TANAMAN CABAI MERAH SETELAH VEGETATIF AKHIR PADA ANDISOL, LEMBANG - Henly Yulina, Rina Devnita, dan Rachmat Harryanto (Program Studi Agroteknologi Faperta UNIBBA, 2021)
This study aims to determine the effect of steel slag and rice husk bokashi on available water, plant biomass and the relationship between available water and red chili plant biomass after the final vegetative stage in Andisol, Lembang. The study used a factorial randomized block design with two factors. The first factor is steel slag and the second factor is rice husk bokashi, each with 4 levels: 0%, 2.5%, 5.0%, and 7.5%, repeated twice. The results showed that there was an interaction between steel slag and rice husk bokashi on available water and red chili plant biomass after vegetative end and there was a relationship between available water (X) and red chili plant biomass (Y). The combination of steel slag at a dose of 2.5% (t1) and rice husk bokashi at a dose of 7.5% (w3) was the best combination to increase the available water capacity of red chili, while the combination treatment of steel slag was 5.0% (t2) and husk bokashi. rice 5.0% (w2) is the best combination to increase the biomass of red chili plants.